The kingdom of insects as a social and political projection in "The cricket" by Carlos Muñiz and "Fate of a cockroch" by Tawfiq al-Hakim - Nasr, Adel Mohamed Mohamed (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
The purpose of this paper is to analyze comparatively the common interest of Carlos Muñiz and Tawfīq Al-Ḥakīm in criticizing the authoritarianism of the political regime that affected the social and political life of their respective countries. The protagonist in both works is compared to the insect (cricket-cockroach) due to his mediocrity, since no one pays attention to both man and insect, despite their repeated screams. This strategy of resorting to the kingdom of insects to project its criticisms towards the political and social dimensions has been a camouflage device to escape the censoring apparatus of the dictatorial regime.